2023
DOI: 10.31616/asj.2022.0209
|View full text |Cite
|
Sign up to set email alerts
|

The Potency of Platelet-Rich Plasma for Chronic Low Back Pain: A Systematic Review and Metaanalysis of Randomized Controlled Trial

Abstract: Low back pain is one of the leading causes of disability in the world. Regenerative medicine can be one of the novel treatment breakthroughs in patients with low back pain, yet its use is still debatable. We performed a systematic evaluation and meta-analysis to determine the efficacy of platelet-rich plasma (PRP) treatment for patients with chronic low back pain. Comprehensive database searches were performed in four databases. This study was conducted and reported based on the Preferred Reporting Items for S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…For LBP patients, an MCID value of 1.5 for the effect in VAS is recommended, with a 30% change from baseline. 33 Pain intensity decreased at 4 weeks were not significantly different between patients who received PRP injections compared with those who received CS (0.44, 95% CI-0.88 to 1.75, p =0.52) and lidocaine (−0.12, 95% CI-1.94 to 1.71, p =0.90). Pain intensity decreased at 3 months, there was no statistical difference between patients injected with PRP and patients injected with CS (−0.36, 95% CI-0.81 to 0.10, p =0.13) and lidocaine (−0.57, 95% CI-1.30 to 0.17, p =0.13), and there was a significant difference between patients injected with PRP and RF (1.37, 95% CI 0.73 to 2.00, p =0.00).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…For LBP patients, an MCID value of 1.5 for the effect in VAS is recommended, with a 30% change from baseline. 33 Pain intensity decreased at 4 weeks were not significantly different between patients who received PRP injections compared with those who received CS (0.44, 95% CI-0.88 to 1.75, p =0.52) and lidocaine (−0.12, 95% CI-1.94 to 1.71, p =0.90). Pain intensity decreased at 3 months, there was no statistical difference between patients injected with PRP and patients injected with CS (−0.36, 95% CI-0.81 to 0.10, p =0.13) and lidocaine (−0.57, 95% CI-1.30 to 0.17, p =0.13), and there was a significant difference between patients injected with PRP and RF (1.37, 95% CI 0.73 to 2.00, p =0.00).…”
Section: Resultsmentioning
confidence: 79%
“…For patients with LBP, the recommended MCID value for disability indices is 10, a change of 30% from baseline. 33 In this study, all participants had a decrease in disability indices at 4 weeks, 3 months, and 6 months follow-up, but none of the disability indices were statistically significant, except the PRP injections compared with RF were statistically significant at 3 months (0.58, 95% CI 0.0040 to 1.16, p =0.048) and PRP injections compared with CS injections that were statistically significant at 6 months (−1.33, 95% CI −1.83 to −0.83, p =0.00). The findings between-group differences were shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that a complex interaction between GFs and cytokines promotes neovascularization and macrophage-induced disk material phagocytosis [ 19 ]. A meta-analysis of multiple randomized controlled trials done by Singjie LC et al found that PRP is more effective than the control group in treating chronic LBP, as demonstrated by the significant decrease in the pain score difference between the PRP and control groups at one, three, and six months after injection [ 20 ]. In comparison to controls, PRP injection dramatically improves chronic LBP in the first, third, and sixth months following injection.…”
Section: Reviewmentioning
confidence: 99%